Stakeholder analysis for controlling land utilization in Parangtritis sand dunes. Issue 1 (March 2021) - Ningrum, E R; Laili, A; Yasiroh, I I; Wardani, W T K; Al Tumus, M G R; Amri, I; Aditya, B; Putri, R F
Abstract: Land use change in coastal sand dune is a problematic issue that can arise due to inappropriate use. Stakeholders have a large role in the management of sand dune. This study aims to identify and map the role of stakeholders in relation to land utilization in Parangtritis sand dunes. Land use distribution was analyzed using ArcGIS software, while the method used for stakeholder analysis was in-depth interviews. The stakeholders in this study are the Spatial Planning Agency of Bantul Regency (DPTR), the Environmental Agency of Bantul Regency (DLH), Parangtritis Geomaritime Science Park (PGSP), Tourism Awareness Group (Pokdarwis), Save Our Sand Dune Lives (SOSDL), village government, and the local community. The result indicated that many anthropogenic activities were identified on the sand dune area, which in turn can endanger the existence of this landform. Based on the results of the analysis, it shows that the stakeholders included in the role of the main players (key players) are DPTR, DLH, PGSP, Pokdarwis, and SOSDL. Meanwhile, stakeholders included in the subject category are the village government and the local community. There is no communication forum for management, supervision, and control of the sand dune conservation area, as well as integration between stakeholders.